2022
DOI: 10.3390/molecules27082590
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-Conjugated Zinc Oxide Nanoparticles, Biogenically Synthesised Using a Fungus Aspergillus niger, Exhibit High Therapeutic Efficacy against Lung Cancer Cells

Abstract: This study reports the therapeutic effectiveness of doxorubicin-conjugated zinc oxide nanoparticles against lung cancer cell line. The zinc oxide nanoparticles (ZnONPs) were first synthesised using a fungus, isolated from air with an extraordinary capability to survive in very high concentrations of zinc salt. Molecular analysis based on 18S rRNA gene sequencing led to its identification as Aspergillus niger with the NCBI accession no. OL636020. The fungus was found to produce ZnONPs via the reduction of zinc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…This white color is common for ZnO NPs, which are equivalent to earlier biosynthetic ZnO NPs generated from other bioactive materials and have a visible range of 300-400 nm 51 . The real highest absorption peak of synthetic ZnO NPs that verified the generation of ZnO NPs previously ranged from 275 to 365 nm, depending on the biosynthesis technique and reduction reaction (reductant and precursor) utilized 20,33,[52][53][54][55] . For our biosynthetic ZnO NPs, the maximum UV-visible absorption peak was found at 320 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This white color is common for ZnO NPs, which are equivalent to earlier biosynthetic ZnO NPs generated from other bioactive materials and have a visible range of 300-400 nm 51 . The real highest absorption peak of synthetic ZnO NPs that verified the generation of ZnO NPs previously ranged from 275 to 365 nm, depending on the biosynthesis technique and reduction reaction (reductant and precursor) utilized 20,33,[52][53][54][55] . For our biosynthetic ZnO NPs, the maximum UV-visible absorption peak was found at 320 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The antimicrobial capabilities of NPs were influenced by their size, shape, concentration, surface area-tomass ratio, and physico-chemical properties. For example, the size of NPs and their antimicrobial properties are inversely correlated; as the particle size decreased, the inhibitory effect increased 52 . Tiny NPs quickly interacted with the cell surface due to their increased surface reactivity, breaking the cell membrane and causing intracellular component leakage and cell death 33 .…”
Section: Runsmentioning
confidence: 99%
“…The studies have also demonstrated that ZnO nanoparticles can be used as drug delivery systems with controlled release of anticancer drugs. Finally, pH-sensitive Zinc Oxide nanoparticles have been shown to release anticancer drugs like cisplatin in a controllable manner [10][11][12]. In recent years, essential attention has been given to the green synthesis of nanoparticles because it is an eco-friendly method and the non-use of fewer chemical compounds can also have a signi cant impact on the biological properties of materials [13][14][15] In 1999, three research groups independently created mesoporous organosilica compounds from organic bipolar alkoxysilane precursors.…”
Section: Introductionmentioning
confidence: 99%
“…In the following, some research studies are mentioned that have investigated the use of ZnO in cancer. Mishra et al [10] reported in their study about the therapeutic effectiveness of doxorubicinconjugated zinc oxide nanoparticles against lung cancer cell lines. Results show that, in comparison to anticancer drugs alone, the compounds ZnO and doxorubicin have strong therapeutic e cacy to inhibit the growth of lung cancer cells.…”
Section: Introductionmentioning
confidence: 99%